Resources as dual sources of advantage: Implications for valuing entrepreneurial‐firm patents - Hsu, David H.; Ziedonis, Rosemarie H. (Strategic Management Journal, 2013)
Why and how do resources provide sources of competitive advantage? This study sheds new light on this central question of resource‐based theory by allowing a single resource—entrepreneurial‐firm patents—to play distinctive roles in different competitive arenas. As rights to exclude others, patents serve a well‐known role as legal safeguards in product markets. As quality signals, patents also could improve access and the terms of trade in factor input markets. Based on the financing activities of 370 venture‐backed semiconductor start‐ups, we provide new evidence that patents confer dual advantages in strategic factor markets, improved access and terms of trade, above and beyond their added product‐market protection. The study has important implications for empirical tests of resource‐based theory and the measurement of resource value . Copyright © 2013 John Wiley & Sons, Ltd.